2015
DOI: 10.1260/1369-4332.18.9.1371
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of a Novel Circular HSC Column with Double High Strength Spirals

Abstract: During the last decades, great progress has been made in the research and application of high strength concrete (HSC). Due to its high strength, low dilation and brittle nature, substantial more transverse reinforcement is needed for HSC columns to obtain ductile behavior, especially for columns with large axial load ratio and/or located in seismic zones. In this paper, a novel HSC concrete column with double high-strength stirrups is proposed, which features two concentric transverse stirrups. The concrete in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…In recent years, the author's research team conducted axial compression loading tests of confined concrete column confined with two layers of stirrups. The experimental results showed that the column exhibited high ductility and bearing capacity due to the confinement of two‐layer stirrups.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the author's research team conducted axial compression loading tests of confined concrete column confined with two layers of stirrups. The experimental results showed that the column exhibited high ductility and bearing capacity due to the confinement of two‐layer stirrups.…”
Section: Introductionmentioning
confidence: 99%
“…Although a few very fine researchers on assessment of doubly confined concrete columns exists. None of them has applied Non Destructive methods of testing e.g., researches in [3], [22], [23], [24] and [25]. Further the authors' current research provides an opportunity studying the impact upon largest number of samples so far.…”
Section: Introductionmentioning
confidence: 99%
“…It has been well understood that lateral confinement can enhance the strength and ductility of concrete (Mander et al, 1988;Yang et al, 2015). From the experience of several destructive earthquakes (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative, the authors recently proposed a new column form, namely RC columns confined using two layers of stirrups (Yang et al, 2015), which features an outer and an inner layer of steel stirrups. Typical cross-section configurations of the columns are shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation